Innovative and Healthy Cookies Enriched with Blueberry Leaf Powder - Santuccione, Francesco Antonio (2025)
Blueberry (Vaccinium spp.) leaves, a residual biomass of pruning, are a rich source ofpolyphenols, fiber, and minerals. In this study, blueberry leaf powder (BBLP) was incorporatedinto wheat/soy flour-based cookies to develop antioxidant- and fiber-enrichedbakery products. BBLP exhibited 8.2% protein, 44% dietary fiber (predominantly insoluble),and high antioxidant activity (2109 ± 20 mg gallic acid equivalents/100 g sample;6251 ± 42 μmol Trolox equivalents/100 g). Four cookies’ formulations were prepared byreplacing 0%, 2.5%, 5.0%, and 7.5% of the flour blend with BBLP. The total phenolic content,total antioxidant content, physical properties (weight, diameter, thickness, volume, hardness,and color), chemical composition (moisture, ash, minerals, protein, carbohydrate, fat,and fiber content), and sensory properties (taste, texture, aroma, and overall acceptability)were analyzed. All BBLP-enriched cookies qualified as a “source of fiber” according toCodex Alimentarius guidelines and EU Regulation (EC) No 1924/2006 on nutrition andhealth claims for foods. The addition of BBLP significantly affected the cookies’ diameter,thickness, volume, and hardness, likely due to its high insoluble fiber content. Moreover,as BBLP levels increased, the surface color darkened progressively, with increased rednessand decreased yellowness attributed to the presence of anthocyanins. Accordingly, BBLPenrichedcookies showed increased antioxidant capacity, proportional to the amount ofBBLP added, indicating good retention of the bioactive compounds after baking. Sensoryevaluation using Quantitative Descriptive Analysis revealed that cookies with 2.5% BBLPwere rated with the highest acceptability scores, whereas higher concentrations impartednoticeable herbal notes and a darker color, decreasing overall acceptability. In conclusion,BBLP can be effectively incorporated at 2.5% to enhance the nutritional quality and antioxidantpotential of cookies without compromising sensory appeal, contributing to sustainablefood innovation by valorizing residual agricultural biomass.